Increased Goal Tracking in Adolescent Rats Is Goal-Directed and Not Habit-Like - Rode, Analise N.; Moghaddam, Bita; Morrison, Sara E. (Frontiers in Behavioral Neuroscience, 2020)
When a cue is paired with reward in a different location, some animals will approach the site of reward during the cue, a behavior called goal tracking, while other animals will approach and interact with the cue itself: a behavior called sign tracking. Sign tracking is thought to reflect a tendency to transfer incentive salience from the reward to the cue. Adolescence is a time of heightened sensitivity to rewards, including environmental cues that have been associated with rewards, which may account for increased impulsivity and vulnerability to drug abuse. Surprisingly, however, studies have shown that adolescents are actually less likely to interact with the cue (i.e., sign track) than adult animals. We reasoned that adolescents might show decreased sign tracking, accompanied by increased apparent goal tracking, because they tend to attribute incentive salience to a more reward-proximal “cue”: the food magazine. On the other hand, adolescence is also a time of enhanced exploratory behavior, novelty-seeking, and behavioral flexibility. Therefore, adolescents might truly express more goal-directed reward-seeking and less inflexible habit-like approach to a reward-associated cue. Using a reward devaluation procedure to distinguish between these two hypotheses, we found that adolescents indeed exhibit more goal tracking, and less sign tracking, than a comparable group of adults. Moreover, adolescents’ goal tracking behavior is highly sensitive to reward devaluation and therefore goal-directed and not habit-like.